Evolutionary Loss of Acid-Secreting Stomach and Endoskeletal Ossification: A Phosphorus Perspective - Shozo H. Sugiura (Fishes)
Phosphorus is essential for all life forms on Earth, including eukaryotes (animals, plants, fungi, and protists), prokaryotes (bacteria and archaea), and even viruses. Its significance stems primarily from its presence in nucleic acids (DNA and RNA), where it forms a crucial part of the backbone structure. Beyond this, phosphorus plays a pivotal role in countless biological processes, supporting life at its core. In this article, the author explores the possible causes of stomach loss, focusing specifically on phosphorus absorption, vertebral calcification, and reproduction. Large gonads, characteristic of external fertilization, require substantial amounts of phosphorus for gametogenesis in both females and males, particularly in the latter. This demand has driven the evolutionary calcification of vertebrae, which serve as a phosphorus storage organ. Moreover, to efficiently absorb phosphorus from their diets, shellfish-eating fish have evolved to either lose their stomachs or reduce gastric acidity, minimizing the formation of calcium phosphate precipitates in the intestine.